Community police forums` future and legitimacy: Redefining good community policing - Siyanda Dlamini (Cogent Social Sciences, 2024)
In recent years there has been growing research interest in police-community relations on crime fighting and prevention. This was likely the result of the community policing movement, which sought to strengthen ties between citizens and the police, as well as concerns about the legitimacy of such initiatives. Hence, more than twenty-eight (28) years after the attainment of democracy in South Africa, the question beckons: How can criminal justice institutions encourage law-abiding behaviour and what constitutes success in terms of police activity aimed at reducing crime? Answers to questions of this type often revolve around the idea that police-community relations are an important component of crime fighting in South Africa. Hence, this paper aims to gain an understanding of the legitimacy and future of Community Police Forums (CPFs) as the Community Policing strategy for crime fighting and prevention in South Africa. For this paper, a qualitative research approach was adopted, to explore such understanding. The findings collected through focus group discussions and key informant interviews with participants comprising of South African Police Service and Community Police Forums representatives, political leaders and ordinary society members suggest that the legitimacy of the Community Police Forums is partly about perceptions, and partly about reality. This means that in a complex world where ideas concerning institutions are shaped by a growing range of societal trust and confidence, there is a need that strategies to improve the legitimacy of the Community Police Forums including public relations exercises by law enforcement institutions.